Glucose and Lipid Metabolism Abnormalities among Patients with Autosomal Dominant Polycystic Kidney Disease - Magda Fliszkiewicz; Mariusz Niemczyk; Andrzej Kulesza; Anna Łabuś; Leszek Pączek (Karger Publishers, 2019)
Introduction: Autosomal dominant polycystic kidney disease (ADPKD) is the most prevalent monogenic renal disease with a prevalence of 1:1,000 births and it is the 4th most common cause of dialysis-dependent end-stage renal disease (ESDR). Recent reports suggest an association between APDKD and metabolic derangements, particularly impaired glucose metabolism. Methods: In this cross-sectional study we analyzed data obtained from case records of 189 patients with ADPKD, including kidney transplant recipients, managed in an outpatient department. Results: The mean BMI was 25.4 ± 3.9; 25.25 before and 27.7 after transplantation. A fasting glucose level above 100 mg/dL (5.6 mmol/L) was observed in 60 patients (29%) - 27% without transplantation and 41% kidney transplant recipients. Diabetes mellitus was diagnosed in 17 patients (8.9%), including 3 (2.3%) without a history of transplantation and 14 (24.1%) after kidney transplantation (p < 0.01). We observed dyslipidemia in 30% and hyperuricemia in 53% of patients. Conclusion: Demonstrated metabolic abnormalities should be considered in maintenance of ADPKD patients, including kidney transplant recipients.